2021
DOI: 10.1111/jocd.14709
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study examining the expression of STAT 1, 3, 6 in prurigo nodularis lesions with its immunopathogenic and therapeutic implications

Abstract: Background Prurigo nodularis (PN) is a chronic dermatologic condition manifesting as multiple papulonodular lesions occurring on the background of intense pruritus. PN could be primary or secondary. The exact immune pathogenesis of PN is not yet clear, and multiple pathways are proposed with the JAK‐STAT pathway rarely being investigated. Aims In this study, our aim was to assess the role of Th cells in PN by comparing the expression of STAT 1, 3, and 6 in involved and normal skin of primary prurigo nodularis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…One study evaluated the JAK STAT pathway in prurigo nodules to determine if this inflammatory pathway may be prevalent in the disease. 90 The results reported that STAT 2 and 3 were upregulated in PN lesions, as well as corresponding cytokines of Th2, Th17, and Th22. STATs are intracellular transcription factors that propagate extracellular signals from JAK receptors to the nucleus.…”
Section: Current Immunotherapeutics Used For Pnmentioning
confidence: 94%
See 2 more Smart Citations
“…One study evaluated the JAK STAT pathway in prurigo nodules to determine if this inflammatory pathway may be prevalent in the disease. 90 The results reported that STAT 2 and 3 were upregulated in PN lesions, as well as corresponding cytokines of Th2, Th17, and Th22. STATs are intracellular transcription factors that propagate extracellular signals from JAK receptors to the nucleus.…”
Section: Current Immunotherapeutics Used For Pnmentioning
confidence: 94%
“…STATs are intracellular transcription factors that propagate extracellular signals from JAK receptors to the nucleus. 90 Numerous cytokines activate the JAK response. Th1, Th2/Th17/Th22, and Th2 cellular pathways are mediated by STAT 1, 3, and 6, respectively.…”
Section: Current Immunotherapeutics Used For Pnmentioning
confidence: 99%
See 1 more Smart Citation
“…The recalcitrant itch of this disease is not relieved by conventional anti-pruritic therapies. Although the pathogenesis is not fully understood, 1 study reported that STAT 2 and 3 were upregulated in pruritic nodules, as well as the corresponding cytokines Th2, Th17, and Th22 ( 33 ). Two clinical trials have been conducted to evaluate the efficacy of JAK inhibitors in prurigo nodularis ( 32 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…These cytokines (IL-4, IL-13, and IL-31) have been found to induce local pruritus in human or in somatic animal models with subcutaneous injections [28,29,30] . Recent studies have revealed that IL-4 and IL-13 can exert intercellular inflammatory transduction by binding to IL-4RA, and that IL4-RA can further induce chronic inflammatory and pruritic responses by further activating the JAK1 signalling pathway [31,32,33] . The mechanism of dupilumab is primarily targeted to antagonize IL-4/13R.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%